The changes in the focus of Slovak organisations on talent management - Zdenko Stacho; Katarína Stachová; Ján Papula (Verslas: Teorija ir praktika / Business: Theory and Practice, 2018)
Distinguishing an organisation from the competition, and building a position noticeably ahead of it entails the identification, attracting, education, development, and especially retaining of quality and talented employees. The objective of the article is to analyse the link between the region of operation of the organisation and its focus on the activities related to talent management, and to specify the overall change in the focus of organisations on talent management in time. Several partial objectives, such as a questionnaire survey conducted in Slovak organisations between 2013 - 2017, were fulfilled in order to accomplish this objective. Statistical hypothesis testing aimed at specifying the relationship between the region of operation of the given organisation and the execution of activities related to talent management in it, and the focus of the organisation on career planning of all the categories of employees, confirmed a link between the analysed variables. Positive changes in the selected attributes in time were evaluated by the fixed-base index.
Keywords: E24; J24; M12; 650; development; human resources; Slovak organisations; talent management